Current principles of photoprotection (Journal of Face Aesthetics, 2023)
Solar radiation is an important factor affecting human health. Under the influence of ultraviolet UVR vitamin D is synthesized in the skin, but its negative consequences are the possibility of skin burns, photoaging, damage to cell structures, including the DNA chain, and secondarily carcinogenesis. Protection from sunlight can be provided by using creams with UV filters, clothing with accessories, and avoiding overexposure to the sun. This paper presents the current principles of photoprotection based on current literature data.
Keywords: photoprotection; sunscreens; ultraviolet radiation